IMPROVING STUDENTS' SCIENCE LEARNING OUTCOMES USING ANIMATED INTERACTIVE MEDIA ON THE DEVELOPMENT OF LIVING CREATURES MATERIAL FOR CLASS IV PRIMARY SCHOOL 71 MACCINI SOPPENG DISTRICT - Andi; Irmawanty; Nur, Andi Muafiah (Jurnal Keguruan dan Ilmu Pendidikan (JKIP), 2022)
The main problem in this study is that the learning media used by teachers are less interesting and varied, so that students are less interested or focused on learning so that students' science learning outcomes are low. The aim of this study was to find out whether the application of interactive animated media as a learning medium can improve science learning outcomes for students in grade IV UPTD SPF SDN 71 Maccini, Soppeng Regency. The type of research conducted was classroom action research (CAR) with two cycles which included three meetings. The subjects of this study were 28 class IV UPTD SPF students at SDN 71 Maccini, Soppeng Regency. Data obtained by observation sheets, tests and documentation. The results showed that there was an increase in students' learning activities through the application of interactive animated media as learning media where in the first cycle the average percentage of students' learning activities was 70.36% and in the second cycle it increased to 91.07%. The average score of science learning outcomes in cycle I was 68.93 and 19 students who completed or 32% were in the poor category, and the average score in science learning outcomes in cycle II increased to 88.68 and 24 students who completed or 86% were in the very high category. From the results of this analysis, it was concluded that the science learning outcomes of fourth grade UPTD SPF students at SDN 71 Maccini Soppeng Regency could be improved through the application of interactive animated media as learning media. So, it can be concluded that the application of interactive animated media as a learning medium can improve students' natural science learning outcomes and increase students' learning activities.